Linking Creatinine‐to‐Body Weight Ratio With Diabetes Incidence: A Multiethnic Malaysian Cohort Study - Noraidatulakma Abdullah; Ying‐Xian Goh; Aisyatul Najihah Khuzaimi; Azwa Shawani Kamalul Arifin; Nurul Ain Mhd Yusuf; Nazihah Abd Jalal; Norliza Ismail; Nurul Faeizah Husin; Mohd Arman Kamaruddin; Rahman Jamal (Journal of Diabetes)
ABSTRACT Background Emerging evidence suggests that the creatinine‐to‐body weight (Cre/BW) ratio is a predictor for incident diabetes in the Asian population. This study examined the association between Cre/BW ratio and incident diabetes, as well as the relationship between Cre/BW ratio and skeletal muscle and body fat mass in a multiethnic Malaysian cohort. Methods A total of 13 047 eligible participants were selected from 119 560 The Malaysian Cohort participants. Of these, 750 who developed diabetes were selected as cases, while 3750 controls were chosen randomly from healthy participants. This nested case–control study included 4500 eligible participants from The Malaysian Cohort, with a 1:5 case‐to‐control ratio. Participants were stratified into four groups based on Cre/BW ratio quartiles. The Cox proportional hazards model evaluated the effect of Cre/BW ratio on developing incident diabetes. The association between Cre/BW ratio and body composition was assessed using the Pearson correlation coefficient. Results Of the 13 047 eligible participants followed up over 5.3 years, 5.75% (n = 750) developed diabetes. Diabetes incidence decreased with increasing Cre/BW ratios. The Cre/BW ratio was inversely correlated with diabetes risk (HR: 0.403, 95% CI: 0.315–0.515, p < 0.001). Additionally, males and Indians had a higher risk of developing incident diabetes. A significant correlation was observed between Cre/BW ratio and body fat mass (p < 0.001). Conclusions This study reveals an inverse association between the Cre/BW ratio and incident diabetes. It also found a significant moderate correlation between the Cre/BW ratio and body fat mass.